ART CONCEPT OF A WOMAN IN THE INTIMATE LETTERS OF UKRAINIAN NOVELISTS - Ilkiv, A. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Artistic process of a woman myth creation in the intimate letters of Ukrainian novelists such as T. Shevchenko, P. Kulish, M. Kostomarov is investigated in the article. Biographical, literary and aesthetic background of mythologisation of a woman in the novelists’ love messages is identified. Semantic relations of mythologized image of a woman with documentary images of letters and theme problem level of epistolary text are emphasized in the article.